Dual stimulation by autoantigen and CpG fosters the proliferation of exhausted rheumatoid factor-specific CD21low B cells in hepatitis C virus-cured mixed cryoglobulinemia - Del Padre, Martina; Marrapodi, Ramona; Minafò, Ylenia A.; Piano Mortari, Eva; Radicchio, Giovanna; Bocci, Chiara; Gragnani, Laura; Camponeschi, Alessandro; Colantuono, Stefania; Stefanini, Lucia; Basili, Stefania; Carsetti, Rita; et al. (Frontiers in Immunology, 2023)
Hepatitis C virus (HCV) causes mixed cryoglobulinemia (MC) by driving clonal expansion of B cells expressing B cell receptors (BCRs), often encoded by the VH1-69 variable gene, endowed with both rheumatoid factor (RF) and anti-HCV specificity. These cells display an atypical CD21low phenotype and functional exhaustion evidenced by unresponsiveness to BCR and Toll-like receptor 9 (TLR9) stimuli. Although antiviral therapy is effective on MC vasculitis, pathogenic B cell clones persist long thereafter and can cause virus-independent disease relapses. We found that dual triggering with autoantigen (IgG surrogate immune complexes) and CpG restored the capacity of exhausted VH1-69pos B cells to proliferate. The signaling mechanism for this BCR/TLR9 crosstalk remains elusive, since TLR9 mRNA and protein as well as MyD88 mRNA were normally expressed and CpG-induced phosphorylation of p65 NF-B was intact in MC clonal B cells, whereas BCR-induced p65 NF-B phosphorylation was impaired and PI3K/Akt signaling was intact. Our findings indicate that autoantigen and CpG of microbial or cellular origin may unite to foster persistence of pathogenic RF B cells in HCV-cured MC patients. BCR/TLR9 crosstalk might represent a more general mechanism enhancing systemic autoimmunity by the rescue of exhausted autoreactive CD21low B cells.